OC-15 - Risk factors for cancer development after idiopathic venous thromboembolism. Issue 140 (April 2016) - Cosmi, B.; Legnani, C.; Ghirarduzzi, A.; De Micheli, V.; Pengo, V.; Testa, S.; Poli, D.; Antonucci, E.; Prisco, D.; Tripodi, A.; Prandoni, P.; Palareti, G.; et al.
Abstract : Introduction: Idiopathic venous thromboembolism (VTE) is associated with the risk of cancer but the risk factors for cancer development in such patients are still uncertain. Aim: To assess risk factors for the development of cancer after a standard course of anticoagulation in patients with first episode of idiopathic VTE. Materials and Methods: Subjects were enrolled in the three large prospective multicentre studies: PROLONG (NEJM 2006) PROLONG II (Blood 2010) and DULCIS (Blood 2014). Women whose index event was hormone related were excluded from the analysis. The development of cancer was recorded during a 2-year follow-up. Results: 1, 805 patients were enrolled (M/F: 510/453), mean age: 62, median: 67; range:18-87 years). Cancer developed in 55 patients (3% ; 1.7% pt-years) of whom 15 (2.0%; 1.1 % pt-years) had PE with or without DVT and 40 (3.8%; 2.1% pt-years) had DVT without PE (p = 0.03). The development of cancer was associated with DVT without PE (HR:1.8; 95% CI: 1.1-3.3) and age > 65 (HR: 2.5; 95%: 1.3-4.9). Among patients with DVT, with or without PE, the development of cancer was associated with the presence of residual vein obstruction > 4 mm (RVO) at compression ultrasound (HR: 1.8, 95% CI: 1.1-3.3) and age > 65 (HR: 2.8; 95% CI: 1.3-6.2). Conclusions: Age > 65 years, DVT without PE and the presence of RVO are significantly associated with the risk of developing cancer after a first episode of idiopathic VTE over a two-year follow-up.